Effectiveness of Modern Dressing on Healing Diabetic Foot Ulcer: A Literature Review - Susanti, Indah; Effan Fahri Mahendra, Rahmad; Burhan, Asmat (Java Nursing Journal, 2023)
Background: Diabetes mellitus is a group of heterogeneous disorders that have indications in the form of increased content of high blood sugar levels. WHO also confirmed DM to be the 7th trigger of death. IDF (International Diabet Federation) data estimates from survey results after North America in 2017 the 3rd place was occupied by Southeast Asia and people with diabetes mellitus with a percentage of 8.5% at the age of 20-29 years in North Africa. One of the treatments for patients with diabetes mellitus can be wound care using Modern Dressing with the Moist Wound Healing method. Methods: The method used in this wound treatment is the Modern Dressing technique with the Moist Wound Healing method. This procedure can clinically grow tissue 30-50%, increase collagen synthesis by 50%, and the rate of re-epithelialization with moist conditions is 2-5 times faster and can reduce the amount of fluid from above the wound surface. Results: evaluation shows that Modern Dressing wound care with the Moist Wound Healing method is in fact able to maintain moist conditions in the wound, reduce inflammation in the wound so that it can improve and accelerate the healing process of diabetic ulcers. Conclusion: The results showed that the Modern Dressing technique with the Moist Wound Healing method was able to improve the healing process of diabetic ulcers. The results also showed that there were significant changes between modern and conventional dressings. The modern dressing group had a much better development than the conventional dressing. The application of the Moist Wound Healing method in patients with diabetic ulcers can provide a much faster wound recovery reaction.